Clinical decision support malfunctions related to medication routes: a case series. (30th August 2022) - Wright, Adam; Nelson, Scott; Rubins, David; Schreiber, Richard; Sittig, Dean F
Abstract: Objective: To identify common medication route-related causes of clinical decision support (CDS) malfunctions and best practices for avoiding them. Materials and Methods: Case series of medication route-related CDS malfunctions from diverse healthcare provider organizations. Results: Nine cases were identified and described, including both false-positive and false-negative alert scenarios. A common cause was the inclusion of nonsystemically available medication routes in value sets (eg, eye drops, ear drops, or topical preparations) when only systemically available routes were appropriate. Discussion: These value set errors are common, occur across healthcare provider organizations and electronic health record (EHR) systems, affect many different types of medications, and can impact the accuracy of CDS interventions. New knowledge management tools and processes for auditing existing value sets and supporting the creation of new value sets can mitigate many of these issues. Furthermore, value set issues can adversely affect other aspects of the EHR, such as quality reporting and population health management. Conclusion: Value set issues related to medication routes are widespread and can lead to CDS malfunctions. Organizations should make appropriate investments in knowledge management tools and strategies, such as those outlined in our recommendations.